Spent Coffee Grounds Biochar Composite Phase Change Material Design Challenges in a Lab-Scale Solar Water Heater System for Thermal Energy Storage - Raphael Angelo Mondragon; Sasipa Boonyubol; Shuo Cheng; Jeffrey Scott Cross (ASEAN Journal of Chemical Engineering, 2023)
Thermal energy storage systems that use composite phase change materials (CPCM), such as paraffin wax and nonbiodegradable high-density polyethylene, are gaining attention in recent years due to the effort to resolve energy issues. There is a need to undertake research and development on how to prepare durable CPCMs from thermo-chemically treated biowastes, a renewable resource. Raw spent coffee grounds (SCG) have been experimented on previously, but more research needs to be conducted on CPCMs prepared from pyrolyzed SCG-biochar (SCGB) for use in a water tank. This research investigated a biodegradable CPCM made from SCGB and carnauba wax in a lab-scale solar water heater system. The carnauba wax loading of 60% was chosen due to the minimized thermal wax leakage from the PCM. Thermal characterization results revealed that the latent heat of SCGB CPCM is 88.47 J/g which was found to be competitive compared to other biodegradable CPCMs reported earlier. The results also show further potential for using SCGB and carnauba wax as a CPCM in a thermal energy storage system.